TINJAUAN FONDASI TIANG PANCANG PADA BANGUNAN RTMC POLDA MALUKU - Lestaluhu, Apriyanti; Frans, Pieter Lourens; Titaley, Henriette Dorothy (Jurusan Teknik Sipil, 2024)
The foundation of the RTMC Polda Maluku building has changed in the length of the piles used during implementation that is not in accordance with the plan, raising the question of whether the pile foundation with its carrying capacity is able to accept the load working on it. The purpose of this study is to obtain the results of calculating the carrying capacity and lowering of pile foundations in the RTMC building of the Maluku Regional Police using the Meyerhoff method based on Sondir test result data, SPT and laboratory test result data. This study shows that the calculation of the ultimate carrying capacity obtained the ultimate carrying capacity value of single piles from sondir data of 305.6 tons, and SPT data of 595.2 tons and laboratory data of 150.88 tons. This shows that the largest carrying capacity results are based on SPT data, then followed by sondir data and the smallest is the carrying capacity based on laboratory data results. The calculation of the decline in the pile foundation with the number of 2 piles shows a single decrease of 0.0062 m and a decrease in the pile group of 0.015 m and the result of the decline in the pile foundation with a total of 3 piles shows a single decrease of 0.0063 m and a decrease in the group of 0.015 m. This shows that the decrease in the foundation of 2 poles and 3 poles is smaller than the allowable decrease of 0.15 m so that the decrease is declared safe.